PENGARUH MODAL, SUMBER DAYA MANUSIA DAN TEKNOLOGI TERHADAP PENGEMBANGAN EKONOMI KREATIF BIDANG KULINER DI PULAU MADURA - Pujiatuti, Solviria; Mayvani, Titov Chuk’s (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
This study aims to empirically examine the impact of capital, human resources, and technology on the development of the creative economy in the culinary sector on Madura Island. The focus of the research is on creative economy actors in four districts of Madura, namely Bangkalan, Sampang, Pamekasan, and Sumenep. The method used is multiple linear regression. Data were collected through a combination of primary and secondary data. Primary data were obtained by directly distributing questionnaires to 40 respondents, with 10 respondents in each district. Sampling was done using the snowball sampling technique. The research results conclude that capital, human resources, and technology have a significant impact on the development of the creative economy in Madura Island. Keywords: local potential, creative economy, culinary